The Cambridge companion to British romanticism - Curran, Stuart (Cambridge companions to literature., 2010)
This new edition of The Cambridge Companion to British Romanticism has been fully revised and updated and includes two wholly new essays, one on recent developments in the field, and one on the rapidly expanding publishing industry of this period. It also features a comprehensive chronology and a fully up-to-date guide to further reading. For the past decade and more the Companion has been a much-admired and widely-used account of the phenomenon of British Romanticism that has inspired students to look at Romantic literature from a variety of critical angles and approaches. In this new incarnation, the volume will continue to be a standard guide for students of Romantic literature and its contexts.